Characterization of the microbial communities and their correlations with volatile flavor compounds and physicochemical factors in Bashang suancai, a traditional Chinese pickle - Liu, Yuan; Yin, Chen; Wang, Jian; Xing, Weihai; Huang, Yali; Yan, Zhiyu; Chen, Jiachen; Han, Yu; Zhu, Weiran; Zhao, Yidi; Zhang, Kai; Tian, Tingting; et al. (Frontiers in Microbiology, 2024)
Bashang suancai is one of the most wellknown traditional fermented vegetables in North China. The study examined the variations in bacterial diversity, physicochemical properties, and volatile flavor compounds (VFCs) of Bashang suancai over a 7-day fermentation period, utilizing Illumina NovaSeq sequencing and headspace solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS). The leading bacterial phyla were Firmicutes, Proteobacteria, and Cyanobacteria, while the predominant bacterial species included Vibrio, Lactiplantibacillus, Cyanobacteriales, Weissella, and Latilactobacillus. The bacterial community diversity decreased significantly following 7 days of fermentation. The microbial profiles were markedly affected by pH, reducing sugar content (RSC), and salt content (SC). A total of 187 VFCs were identified from the specimens. Following five days of fermentation, the taste compounds achieved equilibrium, with isothiocyanates, alcohols, and esters predominating among the volatile molecules.Spearman correlation analysis revealed that a strong link between Latilactobacillus, Levilactobacillus, Lactiplantibacillus, Weissella, and Vibrio with the flavor of pickles.This study established a significant foundation for identifying strains that enhance taste development and improve the nutritional and sensory quality of Bashang suancai.